Magnitude of central obesity and associated factors among adult patients attending public health facilities in Adama town, Oromia region, Ethiopia, 2022 - Mihiret Shawel Getahun; Haji Aman Deybasso; Meyrema Abdo Komicha; Abenet Menene Gurara (BMC, 2023)
Abstract Background Central obesity is excessive accumulation of fat around the abdomen, which is associated with the risk of coronary heart and cerebrovascular diseases. This study determined the magnitude of central obesity among adult patients using the waist-to-hip ratio, which has a superior capacity to measure the risk of developing non-communicable diseases compared to the body mass index used in previous studies in Ethiopia. Methods Institutional-based cross-sectional study was conducted among a sample of 480 adults from April 1 to May 30, 2022. A systematic random sampling technique was used to select the study participants. Data were collected by using interviewer-administered structured questionnaires and anthropometric measurements. The data were entered into EPI INFO version 7 and analyzed by Statistical Software for Social Science Version 25. The associations between independent and dependent variables were checked using bivariate and multivariate logistic regression analyses. Adjusted odds ratio and 95% confidence interval were used to measure the strengths of the association. Statistical significance was declared at a P value of less than 0.05. Results The magnitude of central obesity in this study was 40% (51.2% and 27.4% among females and males, respectively (95% CI 36-44%)). Being a female (AOR = 9.5, 95% CI 5.22-17.9), age range 35-44 (AOR = 7.0, 95% CI 2.9-16.7), 45-64 years (AOR = 10.1, 95% CI4.0-15.2), married (AOR = 2.5, 95% CI 1.3-4.7), high monthly income (AOR = 3.3, 95% CI 1.5-7.3), high consumption of milk and milk products (AOR = 0.3, 95% CI 0.1-0.6), family history of obesity (AOR = 1.8, 95% CI 1.1-3.2) were significantly associated with central obesity among the study participants. Conclusion The magnitude of central obesity was higher in the study area. Sex, age, marital status, monthly income, consumption of milk and milk products, and family history of obesity were independent determinants of central obesity. Therefore, it is important to raise awareness about central obesity through behavior change communication that targets the high-risk population.